1996
DOI: 10.1111/j.1399-3011.1996.tb01107.x
|View full text |Cite
|
Sign up to set email alerts
|

S‐ and C‐glycopeptide derivatives of an LH‐RH agonist

Abstract: The S-and C-glycosylated nonapeptides 1 and 2 were synthesized as analogs of the non-glycosylated LH-RH agonist buserelin (pGlu-His-Trp-Ser-Tyr-D-Ser( tBu)-Leu-Arg-Pro-NHEt) by segment condensation in solution. 1 and 2 differ from this peptide in the amino acid in position 6. In the first case ( l ) , Dserine (tBu) is substituted by D-CySteine carrying a rhamnosyl residue, in the second case (2) D-alanine carrying a galactosyl moiety bound as C-glycoside is incorporated. The bioactivity of both glycopeptides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…An S-glycosylated amino acid derivative has been synthesized by glycosylation of a D-cysteine derivative with the L-rhamnosyl trichloroacetimidate [209]. The Sglycosyl amino acid was used for the synthesis of an 5'-glycopeptide derivative of a luteinizing hormone-releasing hormone (LH-RH) antagonist.…”
Section: S-glycosidesmentioning
confidence: 99%
“…An S-glycosylated amino acid derivative has been synthesized by glycosylation of a D-cysteine derivative with the L-rhamnosyl trichloroacetimidate [209]. The Sglycosyl amino acid was used for the synthesis of an 5'-glycopeptide derivative of a luteinizing hormone-releasing hormone (LH-RH) antagonist.…”
Section: S-glycosidesmentioning
confidence: 99%
“…This work has now led us to explore the influence of glycosylation on the cellular uptake, taking as a starting point our lead (R6/W3) CPP sequence [19][20][21]. Glycosylation of bioactive compounds has been used mainly for increasing either the hydrophilicity, the enzymatic stability of the compound, and/or its delivery into the brain [22][23][24][25]. In the context of CPPs, we have hypothesized that glycosylation may regulate and or affect the internalization of the corresponding glycosylated analogs of (R6/W3) [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Despite early reports on the use of free radical reactions for the synthesis of C-glycosyl amino acids and peptides [86,105], this approach is still rarely used in comparison to the above-mentioned nucleophilic approaches. Linker et al reported a short three-step synthesis of 2-C-branched glyco-amino acids by addition of nitroacetate to various glycals in the presence of ceric(IV) ammonium nitrate and subsequent reduction of the obtained bicyclic isoxazoline N-oxides [106].…”
Section: Scheme 13 Synthetic Route To C-mannopyranosyl Phenylalanine 68mentioning
confidence: 99%